Hubungan Brand Awareness dan Customer Value terhadap Purchase Decision Motor Honda oleh Masyarakat Kabupaten Sanggau - Meiliana, Karwinda; Santika, Dewi (SAFE-Network, 2025)
This study aims to develop a conceptual model to examine the influence of brand awareness and customer value on the purchase decision of Honda motorcycles among consumers in Sanggau Regency. The population in this study includes all Honda motorcycle users in the area, although the exact number is unknown. A total of 135 respondents were selected using a strata quota sampling technique with a purposive sampling approach. Data were collected through questionnaires and interviews, then analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that both brand awareness and customer value have a positive and significant effect on purchase decisions, both individually and simultaneously. The resulting regression model is Y = 0.313X1 + 0.535X2, indicating that these two variables jointly explain a substantial portion of consumer purchasing behavior toward Honda motorcycles in the region. These results highlight that brand strength and perceived product value remain critical components in formulating effective marketing strategies.